The play of ‘dirty politics’: ordinary ethics and the evidence of experience on the workfloor in New Delhi, India - Jaju, Garima (Wiley, 2023)
Abstract This article explores the tensed sociality amongst precariously employed service economy workers in the retail outlets of a prominent eyewear company in New Delhi, India. The bickering staff label the ongoing interpersonal strife ‘dirty politics’. Linked to this are their confident assertions that, in fact, all politics is dirty, and dirty politics is the only type of politics possible – rejecting formal party politics and labour unions as morally vacuous and motivated by utilitarian individualism. Engaging with the anthropology of ordinary ethics, the article demonstrates how the affectively charged experience and talk of petty politicking on the neoliberal workfloor provides critical ‘evidence’ that ‘confirms’ such a politico‐ethical view. Abstrait La « saleté » du jeu politique : éthique ordinaire et preuves tirées de l'expérience au travail à New Delhi, en Inde Résumé Le présent article explore les relations sociales tendues entre les salariés précaires de l’économie des services travaillant dans les points de vente d'une grande chaîne d'opticiens à New Delhi. Ces salariés ont donné aux escarmouches qui les opposent en permanence le nom de « politique sale ». Ils se disent convaincus que, en réalité, le jeu politique est entièrement sale et que la politique ne peut qu’être sale  : le personnel de ces boutiques rejette la politique officielle des partis et des syndicats pour leur vacuité morale et leurs motivations égoïstes et utilitaires. Sous l'angle de l'anthropologie de l’éthique ordinaire, l'article démontre comment l'expérience affectivement chargée et les histoires de mesquineries politiques parmi les classes laborieuses du néolibéralisme apportent des « preuves » critiques « à l'appui » de cette vision politico‐éthique.
Keywords: 4301 Archaeology; 4401 Anthropology; 43 History, Heritage and Archaeology; 44 Human Society